Mak Tucker: capstone - Tucker, Mak, artist (Colorado State University. Libraries, 2021)
The artist's statement: Through material, I explore my own very personal experience with queerness and gender expression. Growing up I developed an aversion to things that are seen as girly and feminine because of my own struggle with gender, and feeling wrong as a woman, the gender I was assigned at birth. Through more thorough investigation of my own identity, I have been able to settle into a more comfortable understanding of myself as a nonbinary individual. I have come back to societally feminine materials with an understanding of how they relate to my experience being genderqueer and knowing that I can love feminine things and express myself through their use without subscribing to their association with womanhood. In my work I include things like pearls and beads and integrate soft colors and imagery to create objects that express my tastes in a way that is in my own control. Through this, I can make new associations for these materials that are disconnected from expectations of femininity. I use imagery of the body in my work to discuss discomfort and alienation from the self, as well as the successes and failures of the physical form in representing the internal self. The body holds our place in the physical world and plays a part in expression and how others view us. This creates a complicated relationship between the internal and physical self, especially when it feels as though the body is not an accurate representation of our internal experience. It becomes difficult to treat the body kindly when it is something that causes frustration, loss of control, and in some ways doesn't feel like your own. In my work I investigate the symbolism of the body in representing emotional experience, and anxieties surrounding the way it fails us and the ways we fail it. The subject of my work often deals with longing, despair, overwhelming emotion, and loss of control. I explore these themes through integration of narrative and character. Fiction, I believe, is often better at expressing truth than reality. I think it is easier to experience emotion and understand difficult feelings in a real way when seeing them through an invented narrative that is disconnected from the complications of reality. These emotions are felt very deeply, and I include fantastical elements in my work to portray the experience of this feeling more accurately.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers